Perancangan Modul Trainer Antarmuka Mikrokontroler Berbasis ESP32 Sebagai Media Belajar Pada Mata Kuliah Interfacing - Kusumah, Hendra; Febriyanto, Erick; Pradana, Restu Adi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2019)
In the computer system study program at Raharja University there are interfacing courses where the material taught is a microcontroller interfacing technique that uses three types of interface protocols on the microcontroller, namely SPI, I2C, and UART interfaces. The learning process at the practical session students must bring their own materials and components that must be arranged before use, in arranging practical materials which is quite a lot especially for some students who do not understand the concept of microcontrollers, this causes the learning process in interfacing subjects to be ineffective and efficient in terms of time and cost to achieve the objectives of interfacing subject learning. From these problems it is necessary to have a learning media in the form of a practical tool or trainer who can support learning and practical activities in interfacing subjects. This study uses prototyping methods, design and observation methods to observe the learning process in interfacing subjects. Thus in this study will produce a microcontroller interface trainer equipped with several supporting components that are interconnected in one circuit board that will be used as a practical tool for students to apply interfacing material to the microcontroller along with the components directly expected by students using this trainer will get a theoretical understanding and application. Keywords: Trainer, Interface, Microcontroller